Typological approaches to measuring construct of psychopathy and personality traits - Pralica, Mihaela (Primenjena psihologija, 2010)
The main research problem is focused on the following question: is it possible to identify specific patterns of interaction between construct of psychopathy and personality traits. The research was conducted on a sample of 223 respondents of both genders (17 to 60 years old). The frame of reference for psychopathy assessment were Klekly- Hare’s criterias for assessment of this disorder, specified in the UPP-2 questionnaire (UPP-2; Novović, Smederevac and Gavrilov, 2007), which includes four dimensions (impulsivity, psychopathic lifestyle, antisocial behavior and psychopathic affect). The frame of reference for personality assessment was the alternative five-factor model (ZKPQ; Zuckerman, 2002), specified in the ZKPQ questionnaire, and consisted of five basic personality traits (activity, aggressiveness/hostility, impulsive sensation seeking, neuroticism/anxiety and sociability). The matrix of squared Euclidean distances (in the common space of factor scores on the principal components of ZKPQ and UPP-2 questionnaires) was a subject of the Ward hierarchical cluster analysis method, extracting three clusters. According to the discriminant function: tendency toward risky and antisocial behaviors and psychopathic affect, the clusters were identified: the group of emotionally reserved person, the group of pro-social oriented person and the group of people prone to antisocial and risky behavior. The results have considerable implications for the preventation programs development and implementation.